What happened to the Iraqi Marsh Arabs and their land? The myth about Garden of Eden and the noble savage - Hanne Kristine Adriansen (Danish Institute for International Studies (DIIS), 2004)
In the aftermath of the 2003 war against Iraq, the newspapers are full of stories about the monstrosities of Saddam Hussein's regime. One example is the destruction of the Iraqi marshlands leading to severe consequences for the human and wildlife population. While the responsibility for the atrocity against the Marsh Arabs is Saddam Hussein's, the desiccation of the marsh environment can be ascribed to a number of the hydro-political decisions made in the catchment area of the Euphrates and Tigris Rivers. Based on an analysis of the discourses of the destruction, it is demonstrated how these have changed after the war and are used in the battle to legitimise the war. This has led to a simplified image of the marshes and the Marsh Arab way of life. As the paper shows, a more complex approach towards the processes leading to this human and environmental disaster is required, if repatriation and rehabilitation of the area are to stand a chance. – – Siden krigen mod Irak blev indledt i marts 2003, har aviserne være fulde af historier om Saddam Husseins uhyrligheder. Et eksempel herpå er ødelæggelsen af Iraks marskområder, der har haft katastrofale konsekvenser for såvel menneskeliv som områdets rige dyreliv. Mens ansvaret for overgreb på befolkningen er Saddam Husseins, skyldes udtørringen af marsksystemet en række hydro-politiske beslutninger, som er blevet taget i hele Eufrat og Tigris' opland. Artiklen viser, hvordan diskurserne om ødelæggelsen af marsken har ændret sig efter krigen, og at de er blevet brugt til at legitimere krigen. Dette har givet et forsimplet billede af såvel marskområderne som marskarabernes levevis. Det konkluderes, at det er nødvendigt med en mere nuanceret forståelse af de problemer, der førte til denne humane og økologiske katastrofe, hvis naturgenopretningen og repatrieringen af marskaraberne skal have en chance.
Keywords: 330